Ant‐mediated ecosystem functions on a warmer planet: effects on soil movement, decomposition and nutrient cycling. (23rd April 2015) - Del Toro, Israel; Ribbons, Relena R.; Ellison, Aaron M.; Cuddington, Kim
Summary Direct and indirect consequences of global warming on ecosystem functions and processes mediated by invertebrates remain understudied but are likely to have major impacts on ecosystems in the future. Among animals, invertebrates are taxonomically diverse, responsive to temperature changes, and play major ecological roles which also respond to temperature changes. We used a mesocosm experiment to evaluate impacts of two warming treatments (+3·5 and +5 °C, set‐points) and the presence and absence of the ant Formica subsericea (a major mediator of processes in north temperate ecosystems) on decomposition rate, soil movement, soil respiration and nitrogen availability. Replicate 19‐L mesocosms were placed outdoors in lathe houses and continuously warmed for 30 days in 2011 and 85 days in 2012. Warming treatments mimicked expected temperature increases for future climates in eastern North America. In both years, the amount of soil displaced and soil respiration increased in the warming and ant presence treatments (soil movement: 73–119%; soil respiration: 37–48% relative to the control treatments without ants). Decomposition rate and nitrogen availability tended to decrease in the warmest treatments (decomposition rate: −26 to −30%; nitrate availability: −11 to −42%). Path analyses indicated that ants had significant short‐term direct and indirect effects on the studied ecosystem processes. These results suggest that ants may be moving more soil and building deeper nests to escape increasing temperatures, but warming may also influence their direct and indirect effects on soil ecosystem processes.